Perlindungan Pekerja Migran Pada Masa Pra Penempatan Berdasarkan Peraturan Pemerintah Indonesia Nomor 59 Tahun 2021 Tentang Pelaksanaan Perlindungan Pekerja Migran Indonesia - Aryawan Arham; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2022)
This research aims are to know how is the form of legal protection for Indonesian migrant workers in the pre-placement time according to the government regulation Number 59 of 2021, and also to know tasks and responsibilities of central and local government in the protection Indonesian migrant worker. This work was normative legal research in which the data were analyzed qualitatively. Result of this study shows that Indonesian government has been conducting all efforts to protect the migrant worker, one of them are protecting them in the pre-placement time, also it is tasks and duties of central and local government.